PENGARUH PARAMETER PERMESINAN TERHADAP FINISHING KEHALUSAN PERMUKAAN ALUMINIUM 6061 - Fajar Budiprasetyo (2023)
In the manufacturing industry, turning is a process that is often used in metalworking. The working principle of turning is rotating the workpiece and the lathe cutting tool as a tool to eat the workpiece. Variables that affect the turning results include spindle speed (Vc), feeding depth (a), feeding rate (F), cooling medium and type of cutting edge. This research focuses on 32 variations of the test parameters on the Aluminum 6061 workpiece by turning the surface of the workpiece. Then the results of the manufacture are assessed for surface roughness. Then the results of surface roughness measurements were analyzed for the contribution of the parameters using ANOVA using Minitab software. From the results of this analysis it was found that the best surface roughness values were obtained for the composition parameters Vc 1120 rpm, f 0.08 mm/put and a 0.1 mm with an average roughness value of 0.517 µm. In addition, the value of the contribution to the surface roughness for the spindle speed is 85.6%, then in the feed grade test the contribution proportion is 2.25% while the depth of feeding the contribution is 9.68%, and the largest contribution to the turning time is the spindle speed. of 76.53%, for the proportion contributing to the consumption rate of 23.47%.